The effect of Citrus reticulata peel extract containing hesperidin on inhibition of SARS-CoV-2 infection based on pseudovirus entry assays - Endah Puji Septisetyani, Hayfa Salsabila Harsan, Dennaya Kumara, Pekik Wiji Prasetyaningrum, Komang Alit Paramitasari, Anisa Devi Cahyani, Khairul Anam, Ria Fajarwati Kastian, Adi Santoso, Muthi Ikawati, Edy Meiyanto (Journal of Applied Pharmaceutical Science, 2025)
Orange (Citrus reticulata Blanco) peel contains a flavonoid glycoside hesperidin (HSD) as the primary component. Upon enzymatic hydrolysis, HSD forms a flavonoid aglycone derivative, hesperetin (HST). These two flavonoids have been predicted to have in-silico affinities for human Angiotensin Converting Enzyme 2 (hACE2) and SARS-CoV-2 spike, crucial proteins involved in the SARS-CoV-2 infection mechanisms. However, in vitro antiviral testing of orange peel extract, HSD, and HST has not been reported. This study presents for the first time a pseudovirus entry assay approach to test the anti-SARS-CoV-2 effect of HSD, HST, and orange peel extract prepared by hydrodynamic cavitation (HCV). We used a nonvirulent pseudovirus model as an alternative to the original SARS-CoV-2 wild-type virus to target the entry point and enable research to be conducted in a lower biosafety level laboratory (BSL-2). Based on HPLC analysis of 1,000 μg/mL HCV, we observed that our HCV contained HSD at about 4% w/w. Moreover, HSD 1 and 10 μM, HST 10 μM, and HCV 1 μg/mL showed inhibition of pseudovirus entry in 293/hACE2 cells with percentages inhibition 25.92%, 37.40%, 27.32%, and 38.97%, respectively. Despite HCV 1 μg/mL showing about 6 % lower inhibitory activity than HSD 1 μM in pseudovirus entry assay, it holds potential as a supplement or source of raw material for HSD as a SARS-CoV-2 antiviral.
Keywords: COVID-19, hesperidin, hesperetin, orange peel extract, SARS-CoV-2 pseudovirus